Inside Cover: Fluorescent‐Ligand‐Mediated Screening of G‐Quadruplex Structures Using a DNA Microarray (Angew. Chem. Int. Ed. 46/2013). Issue 46 (4th November 2013) - Iida, Keisuke; Nakamura, Takahiro; Yoshida, Wataru; Tera, Masayuki; Nakabayashi, Kazuhiko; Hata, Kenichiro; Ikebukuro, Kazunori; Nagasawa, Kazuo
<x xml:space="preserve">Abstract</x> G‐Quadruplexes in the genomic DNA have become new key structures for understanding life phenomena; however, only a limited number of G‐quadruplexes are known. In their Communication on page 12052 ff., K. Nagasawa, K. Ikebukuro, and co‐workers describe a high‐throughput screening method for the discovery of novel G‐quadruplexes by using fluorescent probe molecules and a DNA microarray.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>